Location based mobile information services - Zhang, Guolong (2011)
In recent years, mobile application industry boomed in light speed. The ever-emerging technology has transformed smart phones into mobile hubs for information retrieval. This Final Year Project aims at developing location-based mobile information services. Among all the functions, we focus on developing two applications, namely Augmented Reality Campus Guide and Logo Recognition system.